Climate change, predictive modeling and lemur health: Assessing impacts of changing climate on health and conservation in Madagascar - Barrett, Meredith A.; Brown, Jason L.; Junge, Randall E.; Yoder, Anne D. (Biological conservation, 2013)
► Parasites affect survival of endangered lemurs, but current data are limited. ► Modeled distributions of six important lemur parasites cover up to 86% of forested area. ► Models predict lemur parasite distributions will expand up to 60% with climate change. ► A net expansion of parasite distributions could expose lemurs to new parasites. ► Models important for addressing health impact, protected area design and parasite risk. Deforestation and a changing climate threaten the health and survival of lemurs in Madagascar. An important component of lemur health, parasite infection can reduce fitness and survival outcomes. Future lemur parasite richness, abundance and distribution may be highly influenced by climate change. Current knowledge of lemur parasites is narrow in geographic and temporal scope, with sampling at a limited number of sites, and thus far, there have been no attempts to assess the effects of climate change on lemur parasite distributions. We used geospatial tools to predict the distributions of six lemur parasites of high frequency and pathogenic potential. We then assessed how anticipated climate shifts in Madagascar may alter the distributions of these lemur parasites in the future. Under current climate conditions, we found that the focal parasites exhibited widespread potential distributions across Madagascar, covering 12–26% of surface land area and 40–86% of forested area. Our analyses also showed that parasites responded differently to projected climate changes, with shifts ranging from a contraction of current distributions by 7% to an expansion of 60%. A predicted net expansion in parasite distribution may expose naive lemur hosts to new parasites, which could have a profound effect on lemur health. Those parasites with the greatest potential for harmful effects are predicted to experience the largest expansion in range. Predicting these changing distributions will be critical for assessing population health, improving protected area design, preparing for reintroduction efforts and addressing potential parasite risk in lemurs, humans and domestic animals.